Pengaruh Penerapan Financial Technology (Fintech) Terhadap Rasio Keuangan Perusahaan Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Astusi, Widita Okta; Sidik, M. Muhayin A; Rachman, Artie Arditha (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to examine the impact of the implementation of financial technology (fintech) on the financial ratios of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2019-2022. The methodology used is a quantitative analysis with the collection of secondary data from annual financial statements. The results indicate that fintech positively influences Return on Asset (ROA), Return on Equity (ROE), and Net Interest Margin (NIM), with significance showing that fintech adoption enhances the efficiency and profitability of banks. The conclusion of this research is that fintech adoption can improve banking financial performance, which has positive implications for investors and other stakeholders.